Switching on room-temperature phosphorescence of photochromic hybrid heterostructures by anion-π interactions. (February 2020) - You, Ming-Hua; Li, Meng-Hua; Di, Yi-Ming; Wang, Yi-Wen; Lin, Mei-Jin
Abstract: Room-temperature phosphorescence (RTP) has attracted much attention in the past decades due to its potential applications in optoelectronic devices and bioimaging. So far, most available RTP materials are pure inorganic or organic compounds, few are involved in the organic-inorganic hybrid complexes. The donor-acceptor (D-A) hybrid heterostructures are an emerging class of organic-inorganic hybrid complexes composed of semiconductive organic and inorganic tectons at the molecular level. For these unique hybrids, the primary properties are photochromism and photoinduced electron transfers. Herein, we have demonstrated that the combination of naphthalene diimide (NDI) tectons bearing two divergently oriented pyridyl protons with three polyoxometalate (POM) anions (SiW12 O40 4−, PW12 O40 3− or PMo12 O40 3− ) resulted in three isostructural D-A hybrid heterostructures with an alternate arrangement of segregated POM anions and 1-D H-bonded NDI networks as electron donors and acceptors, respectively. Due to the compact contacts between POM anions and NDI tectons induced by charge-assisted anion-π interactions, not only the photochromic speeds of three D-A hybrid heterostructures have been enhanced, but more interestingly their RTP emissions of have also been switched on, and their photoluminescence quantum yields are dependent on anion-π interaction strengths. Graphical abstract: Due to the compact contacts induced by the charge-assisted anion-π interactions, not only the photochromic speeds of three D-A hybrid heterostructures have been enhanced, but more interestingly their RTP emissions of have been switched on. Image 1 Highlights: Three D-A hybrid heterostructures with segregated POM anions and 1-D H-bonded NDI networks have been synthesized. Compact contacts between POM anions and NDI tectons induced by anion-π interactions lead to the enhanced photochromic speeds. RTP emissions of the three D-A hybrid heterostructures have been swiched on with a high photoluminescence quantum yields. An efficient way to tune RTP emission of hybrid and photochromic speed is described.